If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -2 = 24x + 2 Reorder the terms: -2 + 12x = 24x + 2 Reorder the terms: -2 + 12x = 2 + 24x Solving -2 + 12x = 2 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. -2 + 12x + -24x = 2 + 24x + -24x Combine like terms: 12x + -24x = -12x -2 + -12x = 2 + 24x + -24x Combine like terms: 24x + -24x = 0 -2 + -12x = 2 + 0 -2 + -12x = 2 Add '2' to each side of the equation. -2 + 2 + -12x = 2 + 2 Combine like terms: -2 + 2 = 0 0 + -12x = 2 + 2 -12x = 2 + 2 Combine like terms: 2 + 2 = 4 -12x = 4 Divide each side by '-12'. x = -0.3333333333 Simplifying x = -0.3333333333
| 2x*2+2x*x+1x+2= | | 0.25x+10x-2=121 | | 4x+32=8x | | 5+.75x=-7 | | x^3+x^2+2x-3=0 | | 0.5x-5x+8=-28 | | 2-3+8= | | 7y+13=13y+7 | | -7-15=8 | | 2x+60=2x^2 | | 4n=6*1 | | (x/4)+6=13 | | 6d-3d+2d= | | 2ax+1=ax+5 | | 2x+4x-7=17 | | 8x-5=0 | | 5n+6=4 | | Xt-5=k | | 9+5=5a+5 | | 19x-41=41 | | 7x+18y=4 | | 19x-41=-41 | | 7y-9=8y-1 | | -2(r+6)=-37 | | 2-2n=n+64 | | 0.33=6 | | 2x^2-10x=6 | | 10x-3=-17 | | (3k-7)/(5)=16 | | 49+1-4c=39c-2 | | 2k+k+4= | | [t+5]+3=12 |